التحليل الاقتصادي لاثر التجارة الخارجية في نمو الناتج المحلي الإجمالي العراقي خلال المدة 2005-2020 - علي, محمد اراس; آوختي, سالار حميد (Sulaimani Journal for Humanities, 2022)
Nowadays, no country can live in economic isolation, all aspects of the country's economy are linked to the economies of other countries, and this leads to the formation of international foreign trade of goods, services, labor and technology, and the national economy grows on the basis of economies from other countries. International trade is one of the factors that increases the level of GDP, the purpose of this research is the impact of foreign trade (exports and imports) on the GDP of Iraq, using the quantitative research approach to analyze time series data (2005-2020) for foreign trade and GDP , which was obtained from the Central Bank of Iraq website, and through the use of the econometric analysis program (E-views), it was concluded that the growth in the rates of exports and imports positively effect on the growth rate of Iraq's GDP.